Perencanaan Hotel 5 Lantai di Jalan Soekarno Hatta Kota Semarang (Indonesian Journal of Civil Engineering Study, 2025)
The economic growth and limited land availability in Semarang City have driven the development of vertical buildings such as hotels and apartments, requiring comprehensive structural planning to ensure durability, earthquake resistance, compliance with SNI standards, and aesthetic appeal. This study aims to design the substructure and superstructure of a 5-story hotel building located on Jalan Soekarno Hatta, Semarang, covering the foundation, columns, beams, slabs, and roof. The planning process utilized primary data from site observations and secondary data from literature and soil investigation results. The design outcomes include the dimensions of primary structural elements, such as beams with dimensions ranging from 250x500 mm to 200x400 mm, columns measuring 50x50 cm, floor slabs with a thickness of 120 mm, and roof trusses made of angled steel profiles sized 80x80x8 mm. Structural calculations were conducted using SAP2000 software to determine moments, shear forces, and torsion values, while foundation planning was performed manually based on local soil data. This study demonstrates that structural planning in accordance with SNI standards can effectively ensure the safety, functionality, and aesthetics of the building.
Keywords: Earthquake Resistance; Reinforced Concrete; SNI Standards; Structural Design; Vertical Buildings